Determinants of demand, efficiency and growth of the Global Takaful Industry - Muhammad, Ibrahim Muye (2016)
Since its introduction over three decades ago, Takaful has witnessed remarkable growth in key markets such as the ASEAN and GCC. According to estimates, the global Takaful market is expected to grow continuously on a double digit momentum of 14%. The total contribution was estimated to be US$26 billion as at the end of 2015 and expected to exceed US$42 billion by the year 2020. Studies have previously investigated the factors that influence industry growth, but what drives Takaful growth across markets largely remains unclear.Therefore, this research aims at exploring the factors that drives the growth and development of this sector in light of demand, governance, and supply. Using the difference GMM and the data envelopment analysis estimation methods. The empirical findings show that economic factors- such as income, financial sector development and inflation- and demographic factors- such as level of education, life expectancy, and old dependency ratio are the strongest predictors of Takaful demand. Religion and young dependency ratio do not appear to strongly drive Takaful demand. With respect to the efficiency and governance characteristics of the industry, the bias-corrected DEA score shows that at best, Takaful firms are inefficient due to their size while the second stage Tobit regression indicate that nonexecutive directors, audit committees, and product diversification do not improve technical efficiency while audit committees and regulatory jurisdiction tends to reduce scale efficiency. However, separation of office of chairman and CEO, board size, organizational age, regulatory jurisdiction and firm size have positive effect on technical efficiency, while non-executives, Shari’ah board, product diversification and institutional ownership improves scale efficiency. Further, the relative effect of the board characteristics, for example ratio of non-executives on the technical and scale efficiencies of Takaful firms depends on its interaction with other governance characteristics like board size. Therefore, the outcome of governance mechanism on the efficiency of these firms may involve several other company-specific factors.Finally, for the supply of Takaful products and services, the empirical result from the difference GMM estimation indicates that globalization and institutions are indeed important for the growth of this sector. Financial openness and institutional quality are found to be positive and significant while trade openness appears to be negatively significant. The negative effect from trade openness may be linked to ineffective trade policies in these countries. Furthermore, in terms of the sequence of openness, the empirical result from the GMM estimation fails to support the simultaneous openness hypothesis of Rajan & Zingales, rather, Mckinnon’s sequencing hypothesis seem more appropriate.The results underscore the significance of economic & demographic factors, and globalization in fulfilling the growth potentials of Takaful or in increasing the growth momentum of Takaful. Given that globalization and institutions are also important to the growth of Takaful, then effective globalization and institutional reform policies can be important for policymakers in attempting to accelerate Takaful growth, financial development and savings. The findings from this study could have important commercial and policy implications to countries that have already adopted Takaful insurance.